Synthesis and Complexation of a Bulky Silyl Phosphanide and Extended PNNNP Carbazole-based Ligand - Churchill, Olivia (2024)
In this work, the synthesis of the bulky phosphanide, [(iPr3Si)2P−] was investigated and optimised, leading to the isolation of the sodium phosphanide X2.14. This ligand was explored in preliminary coordinations with Co2+, Fe2+ and Zn2+ resulting in dimeric (X2.21, Co2+) and monomeric (X2.22, Fe2+ and X2.23, Zn2+) products respectively characterised by X-ray crystallography.